Utilización de Apps en clase para potenciar la metacognición y el aprendizaje significativo del alumnado - Usán Supervía, Pablo; Bordás, Carlos Salavera (Sensos-e, 2019)
The main objective of this article is to know the functionality of the educational applications used in university teaching that complement the teaching-learning process of the student in two subjects of the Teaching Degree at the University of Zaragoza: Educational Psychology and Development Psychology. Gamification is understood as the application of the resources of games in non-ludic contexts enhancing the teaching-learning process of students that is also used in the learning of psychological skills such as metacognition and meaningful learning. The applications used are: Quizizz, for the purpose of knowledge consolidation; Mentimeter, which allows the interaction between the student and the teacher in the classroom and Socrative, reviewing the contents of the subject at the end of it. The conclusions encourage an improvement of the motivation and students of the subject although it is an initial phase that can be extended to more subjects next academic year. p align="justify"> Full Article